SPECIFIC FEATURES AND STRUCTURAL PATTERNS OF IDIOMS IN MODERN ENGLISH - Pazilova Nasibaxon Muhammadqosimovna; Qodirova Fotima Xamidjonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is devoted to the investigation of idiomatic expressions and different viewpoints on idioms. It studies specific features, classification, and structural patterns of idioms.